Morphometric Characteristics of the Aziana Valley Basin: هبه محمد فياض, اسحق صالح العكام (Journal of the College of Education for Women, 2021)
The present study aims at examining quantitatively the morphometric characteristics of Iziana Valley basin that is located in the northern part of Iraq; particularly in south of Erbil Governorate. This basin is considered one of the small sub-basins where its valleys run on formations of the Triple and Quadrant Ages, which are represented by the Bay Hassan formations, and the sediments and mixed sediments of the cliffs, respectively. The area of ​​the Iziana basin amounts to (36.39 km2) whereas the percentage of its rotation reaches (0.17); a low percentage, which indicates that the basin diverges from the circular to the rectangular shape. The value of the elongation ratio of the basin reaches (0.38) while the terrain ratio of the basin is (0.03), a low percentage that entails the weakness of its erosion processes and the small volume of the carried and transported sediments. As for the relative topography of the basin, it was (1.08), which is also a low value. It indicates a relatively large area of ​​the basin and the impressive strides that it has made in its erosion cycle. The total river levels of the basin reach (5) ranks, and their numbers vary from one rank to another. Moreover, the total length of the drainage networks in the basin reached (187.4 km), and the prevailing drainage patterns in the basin are the tree and parallel patterns. The researcher has adopted spatial, formal, topographical, and river net-work properties for the purpose of first determining the shape of the basin, the stage of its erosion, its secondary basins, and its terrestrial features that have been developed as a result of the contrast between the erosion and sedimentation processes.